Forecasting Pacific saury (Cololabis saira) fishing grounds off Japan using a migration model driven by an ocean circulation model - Kakehi, Shigeho; Abo, Jun-ichi; Miyamoto, Hiroomi; Fuji, Taiki; Watanabe, Kazuyoshi; Yamashita, Hideyuki; Suyama, Satoshi (Ecological modelling, 2020)
lMigration characteristics of Pacific saury are analyzed using fishery data.lA migration model is developed using migration characteristics.lEarly Pacific saury fishing grounds are forecast using the migration model.lForecast saury fishing ground locations are consistent with actual fishing grounds.lThe migration model will lead to improve the efficiency of the Pacific saury fishery. Pre-fishing season (June and July) Pacific saury Cololabis saira occur offshore, east of Japan, before migrating west to nearshore waters where they are exploited by Japanese fishers in the autumn (September–November). To forecast the location of these fishing grounds we develop a migration model using oceanographic (temperature and current velocity) and fisheries (pre-fishing Pacific saury distribution obtained from stock assessment surveys) data, and migration characteristics determined from fishery data analysis. We speculate that Pacific saury migrate seasonally, first north, staying within a certain temperature zone from May to July, then west, remaining within a preferred but gradually increasing temperature zone. We tune our model using hindcast calculation to reproduce actual fishing grounds around Japan. In July 2018 we forecast the locations of early Pacific saury fishing grounds from August to September. Our forecast fishing grounds were subsequently validated by actual positions of the fishing grounds. Our model successfully forecast the locations of early fishing grounds along the Kuril Islands archipelago, and forecast particles that reached an offshore region roughly predicted offshore fishing grounds. This model also identified Pacific saury migration route trajectories in detail, and that these two fishing grounds in 2018 were formed from geographically separated pre-fishing season shoals via different migration routes. We believe that applying our model will improve the efficiency of the Pacific saury fishery and fleet operation through savings in vessel fuel and time spent searching for shoals.